(untitled) - Vergara , B. S. (Los Banos, Philippines, 1985)
This review has been an important reference in understanding the rice plant. It has had a small but continuing demand. Many new reports on the flowering response of the rice plant have been published this edition includes another 103 publications.
Keywords: Rice,Cây lúa,Plant photoperiodism; Flowering time